How poilitical connection moderate audit committee characteristics and csr: evidence from Indonesian companies - Arief Nurhandika; Vigory Gloriman Manalu (Jurnal Mantik, 2023)
This study aimed to examine the moderation of corporate political connections on the relationship between audit committee characteristics and CSR. This article has developments from various literature on the relationship between corporate governance and CSR; one of those is the audit committees in recent years, which have been synonymous with financial reporting and process audits. This study also uses agency theory, Resource Dependency Theory (RDT), and Social Exchange Theory (SET). The results show a significant positive effect of audit committee independence and expertise. Moreover, political connection is not effect on CSR. Then, political connection can be low moderate between audit committee independence and CSR and political connection can be hight moderate between expertise and CSR